ADOPTION INNOVATION STRATEGY IN ORGANIC FARMING INNOVATION BASED ON SUSTAINABLE EXTENSION ON DRY LAND IN GUNUNGKIDUL REGENCY - Nurlaela, Siti; Sujono, Sujono; Lestari, Tri; Damayanti, Era Rizqi; Panicara, Salsadila (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The excessive use of chemical fertilizers poses a threat to land integrity, leading to soil quality degradation. To counter this trend, farmers must transition towards organic farming practices. This study aims to examine the evolving process of adopting innovations in organic cultivation among farmers in dry land areas of Kalurahan Giritorto, Kapanewon, Purwosari, Gunungkidul Regency. Employing a qualitative descriptive approach, the research takes the form of a case study. Data collection involves interviews with 7 (seven) informan represent the farmer group, observations, and focus group discussions (FGDs), with triangulation techniques. Findings indicate that the adoption of organic farming innovations is feasible, albeit in a semi-organic manner. Farmers adjust their practices to align with environmentally friendly agriculture, gradually reducing the reliance on chemical fertilizers while increasing the use of organic alternatives. Despite positive acceptance and awareness, implementation encounters various obstacles, with economic constraints being the most significant. The study identifies three distinct groups of adopters: early innovator/adopter farmers, early majority farmers, and late majority/slow farmers. These groups exhibit differing characteristics in terms of farming experience, age, group dynamics, and socioeconomic conditions. For the first group, a sustainable extension design is recommended to foster continued innovation. The second group should concentrate on reinforcing motivation and learning from the early adopters. The third group, concerted efforts from extension workers and government interventions are essential to offer intensified assistance. This targeted approach aims to facilitate the continued adoption of organic agricultural innovations by providing capital for later adopter farmers because of low economic conditions.